DUAL RECIPROCITY BOUNDARY ELEMENT METHOD FOR SOLVING TIME-DEPENDENT WATER INFILTRATION PROBLEMS IN IMPERMEABLE CHANNEL IRRIGATION SYSTEMS - Irene, Yanne; Manaqib, Muhammad; Alamsyah, Mochammad Rafli; Wijaya, Madona Yunita (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
The mathematical model of water infiltration in a furrow irrigation channel with an impermeable layer in homogeneous soil is formulated as a Boundary Value Problem (BVP) with the Modified Helmholtz Equation as the governing equation and mixed boundary conditions. The purpose of this study is to solve the infiltration problem using the Dual Reciprocity Boundary Element Method (DRBEM). The results show that the highest values of suction potential and water content are located beneath the permeable channel, while the lowest values are found at the soil surface outside the channel and beneath the impermeable layer. The values of suction potential and water content increase over time t and converge, indicating stability in the infiltration process. These findings align well with real-world scenarios, demonstrating that the developed mathematical model and its numerical solution using DRBEM accurately illustrate the time-dependent water infiltration process in impermeable furrow irrigation channels.